Celebrity endorsements in emerging markets: Align endorsers with brands or with consumers? - Roy, Subhadip; Guha, Abhijit; Biswas, Abhijit; Grewal, Dhruv (Journal of International Business Studies, 2019)
This paper investigates country-of-origin (CO) effects as they relate to celebrity endorsements. Across multiple studies in emerging markets, the authors show that consumers’ evaluations depend on the match between (1) celebrity CO and consumer CO (termed consumer CO fit), and (2) celebrity CO and brand CO (termed brand CO fit). If there is a trade-off between consumer CO fit and brand CO fit, the authors identify contingencies (e.g., ethnocentrism levels) that determine which type of CO fit leads to higher evaluations. Furthermore, the authors develop prescriptions for segmentation in emerging markets and specify when these prescriptions differ from those prescribed by prior international business research.